2015
DOI: 10.4313/teem.2015.16.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Characteristics of Non-contact Electrocardiographic Measurement

Abstract: The ability to take electrocardiographic measurements while performing our daily activities has become the peoplechoice for modern age vital sign sensing. Currently, wet and dry ECG electrodes are known to pose threats like inflammations, allergic reactions, and metal poisoning due to their direct skin interaction. Therefore, the main goal in this work is to implement a very small ECG sensor system with a capacitive coupling, which is able to detect electrical signals of heart at a distance without the conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…As the layers of the insulation materials increase, the distance between the electrode and the skin increase, which finally causes the decrease of the effective capacitance and therefore leads to the deterioration of the ECG quality. This result was consistent with the existing research that had been reported ( Chi et al, 2009 ; Mathias et al, 2015 ; Wang et al, 2019 ). And in our study, for three layers of the insulating material, the ECG signals still had recognizable ECG characteristics, which could be used for further analysis.…”
Section: Discussionsupporting
confidence: 94%
“…As the layers of the insulation materials increase, the distance between the electrode and the skin increase, which finally causes the decrease of the effective capacitance and therefore leads to the deterioration of the ECG quality. This result was consistent with the existing research that had been reported ( Chi et al, 2009 ; Mathias et al, 2015 ; Wang et al, 2019 ). And in our study, for three layers of the insulating material, the ECG signals still had recognizable ECG characteristics, which could be used for further analysis.…”
Section: Discussionsupporting
confidence: 94%
“…In particular, as the elderly population gradually increases in more and more countries, home health care management for these elderly people has attracted increasing attention. With the continuing advances in device miniaturization and wireless technologies, wearable on-body ECG devices for long-term use that have been devised to capture and monitor the electrical activity of the heart may help to establish diagnoses in patients, and considerable progress has been made in this field [4,5,6,7]. However, despite advancements in wireless technology and electronics miniaturization, the development of daily ECG monitoring equipment is still limited by the inconvenience of and patient discomfort caused by wet adhesive electrodes [8], which has led to new requirements for high-performance ECG electrodes with biological compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Surface electrodes that can acquire electrophysiological (EP) signals have many applications ranging from diagnosing neuromuscular disorders [1,2], artificial muscle [3,4], to stimulation of hand rehabilitation [5]. The conventional electrodes are fixed on the body surface by caps, belts, or tapes [6], which lead to inconvenient life of the people as their relatively thick and rigid nature, limited options in mounting locations, and discomfort in long-term usage on the soft, curved, and dynamic human body [7]. The ideal surface electrode is desired to have excellent mechanical adaptability (stretchability > 30%, and conformability with skin wrinkles) and keep electrical stability in recording EP signals during body motion.…”
Section: Introductionmentioning
confidence: 99%
“…The feasible range of geometric parameters for the stretchability and conformability of the network-shaped electrode: the effects of (a) line width w, (b) height-space ratio η, and (c) scale ratio β 6. Complexity…”
mentioning
confidence: 99%